Metode Seismik Dalam Usaha Pendeteksian Reservoir Minyak Dan Gas Bumi (Penerapan Metode AVO) - Awali Priyono (Jurnal Matematika & Sains, 2000)
In this paper, a study of AVO (Amplitude Versus Off-Set) technique as hydrocarbon detection will be presented. The study have been carried out in the carbonate and sandstone reservoirs. AVO analysis, as showed in the range limited off set, indicates that dry carbonate, water or gas in the carbonate reservoir can be recognized from their amplitude responses. The difference in Poissons ratio value between water and gas in the carbonate reservoir is relative small, therefore care must be taken in the analysis. The study shows that, in the case of sandstone reservoar, the AVO response does not depend on the gas saturation, but this is not the case for oil saturation. AVO inversion using Damp Approximation Inverse (DAI) gives good accuracy, therefore this method is very helpful in estimating the elastic parameters such as Poissons ratio and modulus Young in relation to reservoir characterization.